Pengembangan Syringe Pump Berbiaya Rendah sebagai Sistem Pendukung Pemintalan Listrik - Dewa Pascal Ariyanto; Panji Setyo Nugroho; Della Astri Widayani; Luluk Arifatul Hikamiah; Jasmine Cupid Amaratirta; Dewanto Harjunowibowo; Yulianto Agung Rezeki (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2024)
Electrospinning is one of the techniques used to fabricate nanofibers. The syringe pump is one of the main parts of electrospinning, responsible for injecting the solution into the chamber with high precision. The syringe pump has a simple operating system, but it has a high price on the market. Its high price has been one of the obstacles for research groups in the fabrication of nanofibers. Hence, this research aimed to solve the problem of expensive syringe pumps by developing a low-cost syringe pump using affordable components. This research utilized methods from a literature study of syringe pump design, including the manufacturing and assembly of both hardware and software components. It also involved testing the calibration, optimization, and performance of the syringe pumps. An analysis of each stage was carried out until a conclusion was obtained. This syringe pump built in this research used a NEMA 17 stepper motor and TB6600 motor driver to control the flow rate. The total cost to develop this low-cost syringe pump was IDR632,300. Test and calibration were measured at a flow rate ranging from 1 mL/h to 5 mL/h using distilled water, resulting in an accuracy value of 96.7% and a precision value of 95.0%. Further research should utilize gear wheels to reduce the load of the motor stepper so as to prevent prolonged heated conditions. The results of this research can also be used as insight for researchers to develop another low-cost tool in other research fields.